Study on Association Between GSTP1 (rs1695) and Late-Onset Alzheimer Disease and Interaction With APOe4 - Zahra Jafarian; Ali Kowsari; Kourosh Kamali; Hamid Reza Khorram Khorshid (University of Social Welfare & Rehabilitation Sciences, 2016)
Objectives GSTs are detoxification enzymes that remove excess reactive oxygen species (ROS) from cells. Evidence suggests that oxidative stress plays a role in several stages of the neurodegenarative disease like Alzheimer disease. Free radicals and similar molecules are classified as reactive oxygen species (ROS), which can cause oxidative modifications in the cell. In this study we have investigated the association between GSTP1 (rs1695) and AD risk for  genetic variant in Iranian population. Methods & Materials The patient group consisted of 280 cases for GSTP1 gene investigation, whose Alzheimer disease had been approved by psychologists based on clinical test (DSM-IV). The control group included 168 healthy individuals, satisfying the condition of not having any psychological disorders. Individuals’ genotype have been determined by PCR-RFLP method. Statistical analysis was done by logistic regression using OpenEpi 2.3.1 and SPSS 16. Results Significant association was observed between heterozygote genotype (AG) rs1695 A/G of GSTP1 gene and the risk of Alzheimer disease (P=0.005, OR=0.57[0.38-0.84]).This genotype acts as a protective factor. This observed result was significant in within women group (P=0.02). Significant interaction was also found between heterozygote genotype (AG) rs1695 A/G of GSTP1 gene (protective factor) and absent ε4 allele in our study group (P=0.001). Conclusion Based on our results, we suggest that heterozygote genotype (AG) rs1695 A/G of GSTP1 gene can act as a protective factor for Alzheimer disease in Iranian population.